Stable FLRW solutions in generalized massive gravity - de,Rham C; Fasiello,M; Tolley,AJ (International Journal of Modern Physics D: Gravitation, Astrophysics and Cosmology, 2014)
We present exact Friedmann Lemaítre Robertson Walkers (FLRW) solutions in generalized massive gravity where the mass parameters are naturally promoted to Lorentz-invariant functions of the Stückelberg fields. This new dependence relaxes the constraint that would otherwise prevent massive gravity from possessing exact FLRW solutions. It does so without the need to introduce additional degrees of freedom. We find self-accelerating cosmological solutions and show that, with a mild restriction on the region of phase space, these cosmological solutions exhibit full stability, i.e. absence of ghosts and gradient instabilities for all the tensor, vector and scalar modes, for all cosmic time. We perform the full decoupling limit analysis, including vector degrees of freedom, which can be used to confirm the existence of an active Vainshtein mechanism about these solutions.